THE IMPLEMENTATION OF DIGITAL STORYTELLING IN WRITING RECOUNT TEXT TO SECOND GRADERS OF JUNIOR HIGH (RETAIN, 2015)
Abstrak Penelitian ini menunjukkan bahwa Digital Storytelling telah diimplementasikan dalam proses belajar dan mengajar materi menulis teks recount untuk siswa menengah pertama kelas delapan A di SMP Negeri 26 Surabaya. Dengan demikian penelitian ini bertujuan untuk mendiskrisikan bagaimana guru mengimlementasikan Digital Storytelling dalam pembelajaran menulis teks recount. Penelitian ini menggunakan metode diskripsi kualitatif, meneliti tentang penggunaan Digital Storytelling dalam pembelajaran menulis teks recount. Catatan lapangan dan hasil tulisan siswa digunakan sebagai data dalam penelitian ini. Sebanyak 38 siswa kelas delapan A dipilih menjadi partisipan. Hasil dari penelitian ini menunjukkan bahwa pengimplementasian Digital Storytelling telah dilaksanakan sesuai dengan tahapan-tahapan lesson desain yang disarankan oleh Suleiman (2011). Pada tahapan awal pengimplementasian, guru memperkenalkan digital storytelling, teks recount, dan topik serta kosa kata yang akan digunakan pada pembuatan teks. Dalam menjelaskan materi recount, guru menggunakan bantuan slide powerpoint. Guru meminta siswa untuk menulis teks recount dengan topik yang telah ditentukan sebagai narasi untukdigital storytelling. Guru menerapkan langkah kedua dengan meminta siswa untuk bergabung dalam grup serta meminta siswa untuk menyiapkan materi untuk digital storytelling; memilih teks, membawa headphone, laptop, serta mengambil gambar. Langkah ketiga dilaksanakan dengan memeintahkan siswa untuk mulai merekam narasi dan menggabungkan dengan gambar dengan moviemaker. Langkah keempat dilakukan dengan mengumpulkan video siswa dan menampilkan dua video acak di muka kelas. Guru dan siswa memberi komentar pada video yang ditampilkan. Tahap akhir pengimplementasian dilakukan dengan meminta siswa memperbaiki tulisan pada pertemuan lalu di kertas yang sama dengan sebelumnya. Kata Kunci: Implementasi, Digital Storytelling, Menulis, Teks Recount. Abstract This research is aimed to describe the implementation of digital storytelling in writing recount text to the second graders of junior high school and to describe the students’ writing after the implementation. The design of this research is a descriptive research. To conduct the research, a field note is used as an instrument of collecting data. The research subjects of this research are the students of SMP Negeri 26 Surabaya, the students of VIII A Class. The students and the teacher were chosen because they have been implementing Digital Storytelling in writing recount text. Field note and students’ writing were used as data in this research. 38 students were chosen as participant of the research. The result of this research is that the implementation of digital storytelling to teach writing recount text was conducted properly according to the stages suggested by Suleiman (2011). The observation showed that the teacher conduct the first stage of the implementation by explaining recount text and introduced the students to topic and vocabularies by showing example of recount text in a form of digital story and simple recount text. The teacher used PowerPoint slide in explaining the material. The teacher asked the student to create a recount text using a certain topic chosen by teacher as a narration material of the digital story. At the second stage, the teacher asked the students to join in groups then prepare material to create a digital storytelling; choosing the text for narration, photos, headphones, laptop, etc. The third stage was done in the second meeting since there was not enough time in the first meeting. The teacher asked the students to start recording narration and combining the materials of the video into a good digital storytelling clip. Fourth stage was done by collecting students’ video and showed them in front of the class, the students and the teacher gave comments to the video. The last stage of the implementation was done by assigning the students to revise their text in the same paper as the first text. Keywords: Implementation, Digital Storytelling, Writing, Recount Text.